Multilevel analysis of student and school level factors on students’ academic achievement - M. Mohamadi; R. Naseri Jahromi; Z. Mokhtari; Z. Hesampor; R. Naseri Jahromi (فصلنامه نوآوری‌های آموزشی, 2018)
This study aimed to investigate the factors affecting the academic achievement of students at both school and student levels. Therefore, 600 high school students from 20 schools completed student efficacy scale of Jinks and Morgan's (1999) and personal achievement goal orientation and school goal structure scales of Midgley et al. (2000). Also, the school teachers answered teacher's sense of efficacy scale developed by Tschannen- Moran and Hoy (2004). The results of multilevel analysis revealed that at the student level, there is a positive and significant relationship between academic self-efficacy, mastery goal orientation, performance-approach goal orientation, amount of study time and academic achievement. This relationship was negative and significant for the performance-avoidance goal orientation. Girls were found to have higher academic achievement as compared to boys. At the school level, school type and mastery goal structure had a positive and significant relationship with students’ academic achievement. No significant relationship was found among performance-approach, performance-avoidance goal structure, teacher’s collective self-efficacy and academic achievement of students. The level-1 predictors accounted for 49% of the student-level variance and the level-2 predictors accounted for 79% of the school-level variance.